Surviving the trail : five essential skills to prepare every hiker for adventure's most common perils - Scanlon, Rob (Dr.) (Falcon guide., 2025)
"The statistics are difficult to believe, but every week more than ten hikers die and at least another two hundred require rescue in North America, amounting to more than 500 lives lost and more than 10,000 people rescued every year. Analysis reveals they span the full spectrum of trail experience. The silver lining among this alarming data reveals that most hiker deaths and rescues come from just a handful of preventable causes. This presents an opportunity for this book to make a significant impact. Despite a number of articles published over the years in the attempt to raise trail-goers' awareness of this issue, the data remain unchanged. Every week, hundreds continue to fight to survive among avoidable circumstances while awaiting overwhelmed and understaffed wilderness rescue teams. The most common reasons for hiker death and rescue are falling, drowning, dehydration, heat injury, hypothermia, and a lost hiker. Many hikers venture out inadequately prepared, possess a limited skill set, and exhibit poor decision-making when problems arise. That's what Dr. Scanlon's Surviving the Trail is intended to prevent and - if something untoward happens - ameliorate"-- Provided by publisher.